Cat scratch disease: U.S. clinicians' experience and knowledge. (14th July 2017) - Nelson, C. A.; Moore, A. R.; Perea, A. E.; Mead, P. S.
Summary: Cat scratch disease (CSD) is a zoonotic infection caused primarily by the bacterium Bartonella henselae . An estimated 12, 000 outpatients and 500 inpatients are diagnosed with CSD annually, yet little is known regarding clinician experience with and treatment of CSD in the United States. Questions assessing clinical burden, treatment and prevention of CSD were posed to 3, 011 primary care providers (family practitioners, internists, paediatricians and nurse practitioners) during 2014–2015 as part of the annual nationwide DocStyles survey. Among the clinicians surveyed, 37.2% indicated that they had diagnosed at least one patient with CSD in the prior year. Clinicians in the Pacific and Southern regions were more likely to have diagnosed CSD, as were clinicians who saw paediatric patients, regardless of specialty. When presented with a question regarding treatment of uncomplicated CSD, only 12.5% of clinicians chose the recommended treatment option of analgesics and monitoring, while 71.4% selected antibiotics and 13.4% selected lymph node aspiration. In a scenario concerning CSD prevention in immunosuppressed patients, 80.6% of clinicians chose some form of precaution, but less than one‐third chose the recommended option of counseling patients to treat their cats for fleas and avoid rough play with their cats. Results from this study indicate that a substantial proportion of U.S. clinicians have diagnosed CSD within the past year. Although published guidelines exist for treatment and prevention of CSD, these findings suggest that knowledge gaps remain. Therefore, targeted educational efforts about CSD may benefit primary care providers.